Proceedings of the 9th International Conference on Computer Supported Education 2017
DOI: 10.5220/0006323501250136
|View full text |Cite
|
Sign up to set email alerts
|

Towards Computer-based Exams in CS1

Abstract: Abstract:Even though IDEs are often a central tool when learning to program in CS1, many teachers still lean on paperbased exams. In this study, we examine the "test mode effect" in CS1 exams using the Rainfall problem. The test mode was two-phased. Half of the participants started working on the problem with pen and paper, while the other half had access to an IDE. After submitting their solution, all students could rework their solution on an IDE. The experiment was repeated twice during subsequent course in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Students and staff perceive the assessment to be fair and an accurate assessment of programming skills [63,236,715] and to improve student motivation [52]. Students working on computers produce more accurate code than on paper [360]. In a study by Haghighi and Sheard [236] involving both paperbased and computer-based assessment, students found the computer test environment to be more stressful; however, ten years later, Matthíasdóttir and Arnalds [420] found that students were more comfortable taking exams on a computer than on paper.…”
Section: Assessment Approachesmentioning
confidence: 99%
“…Students and staff perceive the assessment to be fair and an accurate assessment of programming skills [63,236,715] and to improve student motivation [52]. Students working on computers produce more accurate code than on paper [360]. In a study by Haghighi and Sheard [236] involving both paperbased and computer-based assessment, students found the computer test environment to be more stressful; however, ten years later, Matthíasdóttir and Arnalds [420] found that students were more comfortable taking exams on a computer than on paper.…”
Section: Assessment Approachesmentioning
confidence: 99%
“…It is also noteworthy that past studies that evaluated the performance difference between computerized and paper assessments only evaluated the product of student work and not the process in which it was generated [11,20,30], in contrast to the current work. Also, these previous studies evaluated the differences only on code writing problems, while our study focuses on code tracing (and reverse-tracing) problems.…”
Section: Related Work 21 Exam Mode: Paper Vs Computermentioning
confidence: 97%
“…Corley et al found that CS 1 students' problem solving ability was largely unaffected by the different assessment formats in code writing tasks, and that student ability to correctly write syntax was significantly worse in the paper-and-pencil version [11]. Similarly, Lappalainen et al's study found that CS1 students in both paper and computer groups had similar performances in terms of understanding on a Rainfall code writing problem, but the paper group had more syntax and minor cosmetic errors (e.g., misspelled variable name) [30]. In contrast, Grissom et al found that CS 2 students' solutions demonstrated higher levels of understanding in the computerized formats when writing implementations of recursive binary search trees [20].…”
Section: Related Work 21 Exam Mode: Paper Vs Computermentioning
confidence: 99%
See 2 more Smart Citations